The Influence of Copywriting, Content Marketing, and Social Media Marketing on Purchase Decisions in E-Commerce - Zakaria, Putra Chevin; Bhirawa, Sigit Wisnu Setya (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study aims to analyze the influence of Copywriting, Content Marketing, and Social Media Marketing on purchase decisions in e-commerce. Design/Method/Approach : This study uses a causality quantitative method, where multiple linear regression analysis is applied, data is collected from 80 respondents selected using a simple random sampling technique from a population of 337 students of the Management study program of Universitas Nusantara PGRI Kediri class of 2021 who are actively using e-commerce platforms, research variables include purchase decisions as dependent variables, as well as copywriting, content marketing,  and social media marketing as independent variables. Research Finding : The results of the study show that copywriting does not have a significant effect on purchase decisions. In contrast, content marketing and social media marketing have a significant influence on purchasing decisions. Simultaneously, these three variables have a significant effect with a contribution of 58.8%. Theoretical contribution/Originality : This research emphasizes the importance of content marketing and social media marketing in digital marketing, especially in e-commerce and fills research gaps related to the combination of these three strategies. Practitionel/Policy implication : This research provides practical insights for e-commerce business people to prioritize content marketing and social media marketing strategies to increase the effectiveness of digital marketing campaigns. Research limitation : This research is limited to students as respondents so that the results can not be generalized.further research is recommended to expand the scope of respondents and explore additional variables that may influence purchase decisions.